Zone of Inhibition of Ethanol and Ethyl Acetate Extracts of Forest Betel Leaves against Escherichia Coli - Rosalina Y Kurang (Jurnal Penelitian Pendidikan IPA, 2023)
The betel plant is one of the medicinal plants known by the common people. This plant consists of more than 1000 species. One of the species is the betel forest. The part of the betel plant that is commonly used as medicine is the leaves. This study aims to determine the phytochemical content and inhibition of Escherichia coli in the ethanol and ethyl acetate extracts of forest betel leaves (Piper aduncum L.). The method used in the antibacterial test is the good diffusion method. The research showed that ethanol extract of forest betel leaves (Piper aduncum L.) leaves contains secondary metabolites, namely flavonoids, saponins, terpenoids, and tannins, while the ethyl acetate extract contains secondary metabolites, namely flavonoids, terpenoids, and tannins. The ethanol and ethyl acetate extracts of forest betel leaves (Piper aduncum L.) can inhibit the growth of Escherichia coli in the strong category